2021
DOI: 10.4103/jehp.jehp_713_20
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of physical medicine and rehabilitation course for undergraduate medical students

Abstract: BACKGROUND: The objective was to evaluate an innovative physical medicine and rehabilitation (PMR) course for undergraduate students of Tehran University of Medical Sciences and their attitude and knowledge change following course participation. MATERIALS AND METHODS: Ninety-one medical students filled the knowledge, attitude, and satisfaction forms pre- and postintervention. Nineteen medical students, two faculty physiatrists, two residents, two physical therapists, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 24 publications
(24 reference statements)
0
1
0
Order By: Relevance
“…This result was consistent with Razavi et al . [ 16 ] They also found that students’ attitudes differed in the pre-and post-intervention phases to the extent that students considered the PM and R course as one of the options for continuing their studies until gaining their medical specialty in this field.…”
Section: Discussionmentioning
confidence: 99%
“…This result was consistent with Razavi et al . [ 16 ] They also found that students’ attitudes differed in the pre-and post-intervention phases to the extent that students considered the PM and R course as one of the options for continuing their studies until gaining their medical specialty in this field.…”
Section: Discussionmentioning
confidence: 99%